Evaluation of light supply in the public underground safe spaces by using of COPRAS-SWARA methods - Nakhaei, Jalal; Lale Arefi, Shahin; Bitarafan, Mahdi; Kildienė, Simona (International Journal of Strategic Property Management, 2016)
One of the most significant issues in the safe underground spaces is the supply of light during the conditions in which there is no possibility to use national electricity network in crisis. Hence, attention to the source management of light supply possesses worthy importance. Light is one of the important issues in underground safe spaces which must be noticed with particular obligations. In the research, in order to evaluate variety of light supply methods in underground safe spaces, a questionnaire was set in order to weigh affective indexes up and score each method. To determine the best index among different indexes, SWARA method was applied; then COPRAS method was used in order to analyze data of the questionnaire that the best choice among various strategies could be chosen. Results represented that the choice of light supply by the lamp with battery source to provide light for city shelters is the best. According to results gotten from this method, choices of light supply by the fossil fuel light, light supply by the urban power source lamp, light supply by the mirror and light supply by fiber optics have been ranked in second, third, fourth and fifth positions, respectively.